Teaching Economics Rooted in the Local Wisdom of Batu City - Pribawani, Meita Rahima; Wardoyo, Cipto; Rahmawati, Farida (Universitas KH. Abdul Chalim Mojokerto, 2026)
The main issue raised in this study is how the local economic wisdom of the community is influenced by cultural bonds and unique traditional values that are often overlooked in economic dynamics measurements, as well as how economic learning is implemented in Batu City. This study aims to explore the identity and dynamics of local wisdom within the community of Batu City, East Java, which reflects a balance between productive and normative elements. Using a phenomenological approach and qualitative methods, this research uncovers the meanings of identity and socio-economic dynamics through in-depth interviews and observations with several key informants. The findings indicate that the economic dynamics of Batu City’s community include elements rooted in agricultural activities, such as the principles of shared sustenance, labor as a form of indebtedness, sharecropping practices, and cultivating land and planting as sources of livelihood. In addition, the application of traditional values such as three-dimensional harmony also plays an important role in their economic life. Spiritual bonds, social solidarity, and harmony with nature serve as the main pillars shaping their local economic identity. The implication of this study highlights the need for culturally grounded policies to support the socio-economic dynamics of the community in the region.